Expanding the applications of a bioluminescent mouse infection model of acute African trypanosomiasis - Benítez, Diego; Ortíz, Cecilia; Dibello, Estefania; Comini, Marcelo A. (Frontiers in Chemical Biology, 2024)
In vivo imaging technology based on bioluminescence has contributed to the study of different pathophysiological conditions involving inherited or transmissible diseases.Here, we aimed to establish a bioluminescent model of acute African trypanosomiasis for a manifold of applications. African trypanosomiasis is a neglected tropical disease that threatens human and animal health, mainly in sub-Saharan countries, for which new chemotherapies are needed.The model relies on a hypervirulent bloodstream form of Trypanosoma brucei brucei, which constitutively expresses red-shifted luciferase, and an infection-susceptible murine host, Balb/cJ mouse. In vivo and ex vivo imaging techniques were applied to obtain a spatial, temporal, and quantitative (parasite load) resolution of the infection process and to refine the animal endpoint criterion. The model proved suitable for validating the essentiality of the parasite enzyme glucose 6-phosphate dehydrogenase by reverse genetics (tetracycline-inducible double-strand RNA interference) and non-invasively.The efficacy of drugs (monotherapy or a new combination) for the treatment of the acute stage of the disease was successfully explored by in vivo imaging.The new bioluminescent model developed here may represent a valuable tool for speeding up the drug discovery process and the investigation of host-pathogen interactions in the acute stage of African sleeping sickness.